Comparison of molecular testing methods for the detection of EGFR mutations in formalin-fixed paraffin-embedded tissue specimens of non-small cell lung cancer. Issue 5 (5th February 2013) - Lopez-Rios, Fernando; Angulo, Barbara; Gomez, Belen; Mair, Debbie; Martinez, Rebeca; Conde, Esther; Shieh, Felice; Tsai, Julie; Vaks, Jeffrey; Current, Robert; Lawrence, H Jeffrey; Gonzalez de Castro, David
Abstract : Aim: To conduct a methods correlation study of three different assays for the detection of mutations at EGFR gene in human formalin-fixed paraffin-embedded tumour (FFPET) specimens of non-small cell lung carcinomas (NSCLC). Methods: We conducted a 2-site method comparison study of two european conformity (CE) in vitro diagnostic (IVD)-marked assays, the cobas EGFR Mutation Test and the Therascreen EGFR29 Mutation Kit, and 2× bidirectional Sanger sequencing. We blind-tested 124 NSCLC FFPET specimens with all three methods; the cobas test was performed at both sites. Positive (PPA) and negative percent agreements (NPA) were determined for the cobas test versus each of the other two methods. Specimens yielding discordant test results between methods were further tested using quantitative massively parallel pyrosequencing (MPP). Results: PPA between cobas and Sanger was 98.8%; NPA was 79.3%. Overall there were seven discordant results. MPP confirmed an exon 19 deletion in two cases and L858R mutation in four cases. PPA between cobas and Therascreen was 98.9% and NPA was 100%. There was one discordant result. Reproducibility of the cobas test between the two sites was 99.2%. Conclusions: The invalid rates for the cobas test and Therascreen were lower than Sanger sequencing. The cobas and Therascreen assays showed a high degree of concordance, and both were more sensitive for the detection of exon 19 deletion and L858R mutations than Sanger. The cobas test was highly reproducible between the two testing sites, used the least amount of DNA input and was the only test with automated results reporting.